"Woke" Corporations and the Stigmatization of Corporate Social Initiatives. Issue 1 (January 2022) - Warren, Danielle E.
Abstract : Recent corporate social initiatives (CSIs) have garnered criticisms from a wide range of audiences due to perceived inconsistencies. Some critics use the label "woke" when CSIs are perceived as inconsistent with the firm's purpose. Other critics use the label "woke washing" when CSIs are perceived as inconsistent with the firm's practices or values. I will argue that this derogatory use of woke is stigmatizing, leads to claims of hypocrisy, and can cause stakeholder backlash. I connect this process to our own field by considering inconsistencies in our organizations and in our teaching that could garner similar criticisms. After describing the stigmatization process, I consider the moral implications of inconsistencies for CSIs and draw parallels to our field. I end by suggesting next steps for our field in response to the stigmatization of CSIs and to guard against the stigmatization of our own work.